PENERAPAN PEMBELAJARAN KOOPERATIF MODEL JIGSAW PADA MATA PELAJARAN PPKn DI KELAS XI IPS 3 SMA NEGERI 10 PONTIANAK - Emi, Emi; Utomo, Bambang Budi; Atma, Thomy Satra (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study aims to determine the application of cooperative learning jigsaw modelss in PPKn subjects in class xi ips 3 state high scool 10. This research using descriptive method. Data collection techniques used are observation techniques, interview quidelines, documentation and tests. Based on the observations of the researchers, the application of the jigsaw type manifestation. the results of the study show that the teacher carries out all stages of the jigsaw cooperative learning model. Student activities in the classroom show that they hold group discussions and deliver material through presentations.student learning outcomes address completeness 66.67%, in the effective domain show a good attitude that is aimed at obtaining a core of 2.8 for aspect of cooperation, responsibility which is 2.73 and activeness 2.8 in the psychomotor domain. The communication skills of the students have been shown to be good, this is evidenced by the presentation which in indicated by the acquisition of the group presentation in the presentation which iss indicated by the acquisition of a core of 3.2 in theirr ability to express opinions and listen to the opinions of other students and a 3.4 score to answer questions from other students.Â Keywords:Â  Jigsaw Cooperative Learning Model, Learning Activities, Learning Outcomes,PPKn